The dominant logic: Retrospective and extension - Bettis, Richard A.; Prahalad, C. K. (Strategic Management Journal, 1995)
Abstract This paper briefly reviews some history of the concept of dominant logic, and then elaborates some of the ways in which the authors have further developed this concept in recent years. Discussion focuses on the dominant logic as a filter, on the dominant logic as a level of strategic analysis, on the unlearning (forgetting) curve, on the dominant logic as an emergent property of organizations as complex adaptive systems, and on the relationship between organizational stability and the dominant logic. Throughout emphasis is given to the inherent nonlinear nature of organizations and the mental models that they create.